Sharia Accounting Training on Kafalah Contract and Technique for Reading Financial Statements at PT. Jamkrida NTB Syariah Bersaing - Lenap, Indria Puspitasari; Cahyaningtyas, Susi Retna; Atikah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT. Jamkrida NTB Syariah Bersaing is a Regionally-Owned Enterprise (BUMD) engaged in the credit guarantee business sector. This community service activity aims to provide training in sharia accounting for kafalah contract and technique for reading financial statements, which was attended by all elements in the organization of PT. Jamkrida NTB Syariah Bersaing. The methods used in this community service activity include presentation, case and discussion. The contents of the presentation are kafalah contract, both concept and practice, and financial statements. Some of the problems discussed include customer eligibility assessments, collateral, suborgation, and kafalah contract. This activity provides many benefits, especially for employees in the fields of finance and accounting, in the form of a better understanding of sharia accounting and financial statements.